Salience strategy: connectivity, aesthetics and the learning mind - Burnett, Richard Leslie George (My University, 2009)
This dissertation adds to the many arguments already made for the value of art (cultural artifact) in teaching and learning. The special approach developed here concludes with the articulation of Salience Strategy. The argument firstly questions the value of seeing intelligence as a problem-solving faculty. It continues by examining consciousness, memory and the imagination as both the ground and substance of intellection. It argues that, amongst other things, interconnectedness, reiterative pathways and networks are central to the operation of consciousness and therefore, are central to its epiphenomenal attributes like intelligence. As education should strive for greater intellectual functioning so it should, therefore, strive to harness the paradigms of interconnectedness, reiterative pathways and networks. The art object, (device, gesture, statement), it is proposed, is valuable when deployed as hubs in networks of ideas allowing learners to form patterns of unexpected and creative linkages enhancing both memory, curiosity and a capacity for imaginative and associative thinking. Learning becomes movement through a landscape of complex objects and outgrowths. Two salience itineraries are explored in this dissertation. The first in relation to concepts overheard during learner conversations over the duration of a school week, and a second, exploiting my own work as an artist, selected work by the British artist Richard Long, and some of the issues raised in the theoretical discussion of consciousness and networks.
Keywords: aesthetics; art; education; patterns; learning connectivity